2013
DOI: 10.1016/j.virol.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E7 oncoprotein inhibits the anaphase promoting complex/cyclosome activity by dysregulating EMI1 expression in mitosis

Abstract: The anaphase promoting complex/cyclosome (APC/C) is a ubiquitin ligase complex that orchestrates mitotic progression by targeting key mitotic regulators for proteasomal degradation. APC/C dysfunction is a frequent event during cancer development and can give rise to genomic instability. Here we report that the HPV16 E7 oncoprotein interferes with the degradation of APC/C substrates and that the APC/C inhibitor, EMI1, is expressed at higher levels in HPV16 E7-expressing mitotic cells. HPV16 E7 expression causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…It has been recently demonstrated that E7 engages both SAC-independent 28 and SAC-dependent 24 mechanisms to prevent APC/C-dependent degradation of cyclin A and cyclin B. In the latter article, www.tandfonline.com both MAD2 and BUBR1 were found highly expressed in E7-positive cells.…”
Section: Discussionmentioning
confidence: 90%
“…It has been recently demonstrated that E7 engages both SAC-independent 28 and SAC-dependent 24 mechanisms to prevent APC/C-dependent degradation of cyclin A and cyclin B. In the latter article, www.tandfonline.com both MAD2 and BUBR1 were found highly expressed in E7-positive cells.…”
Section: Discussionmentioning
confidence: 90%
“…The HPV E7 protein inappropriately stimulates cell cycle progression in the epithelial mid-layer, while E6 perturbs the Scrib and Par complexes to expand the population of infected cells capable of replicating the viral DNA. Expression of E7 alone has been shown to induce the formation of aberrant spindle poles [61,62], while disruption of Dlg and the Par complex also perturbs mitotic spindle orientation [63,64], all of which contributes to enhanced symmetrical cell division, thus expanding the population of replicationcompetent cells and accounting for the disordered epithelium observed in viral lesions.…”
Section: Cell Polarity and The Hpv Life Cyclementioning
confidence: 99%
“…Another possibility is that E7 influences DDR factor protein stability through effects on protein degradation machinery. E7 has been shown to inhibit the anaphase promoting complex/cyclosome (APC/C) (Yu and Munger, 2013), a ubiquitin ligase complex involved in regulation of mitotic progression, as well as the DDR (de Boer et al, 2016). However, whether E7-mediated inhibition of this complex occurs in a manner dependent on the Rb binding domain is not known.…”
Section: Discussionmentioning
confidence: 99%